Prevalence and Correlates of Sexual Violence Experienced by Female Sex Workers in Iran: Results from a National HIV Bio-Behavioral Surveillance Survey - Hosseini-Hooshyar, Samira (Violence against women, 2022)
Sexual violence increases the risk of adverse health outcomes among female sex workers (FSWs). Using data from the 2015 national bio-behavioral survey, we explored the experience of sexual violence and its associated factors among Iranian FSWs. Lifetime and recent sexual violence were reported by 40.1% and 16.9%, respectively. History of substance use, ever engaging in anal sex, engaging in group sex within the last year, a high number of clients, recent unstable housing, and incarceration increased the likelihood of experiencing recent sexual violence. These findings underscore the need for community-empowerment and policy-level interventions to address violence among FSWs in Iran.